148k views
0 votes
Which expression is equivalent to 6+4.5(32f-14f)

User Azquelt
by
4.8k points

1 Answer

6 votes

Answer:


6 + 4.5(32f - 14f) = 6 + 81f

Explanation:

Let us apply the distributive property to find an equivalent expression for:


6 + 4.5(32f - 14f)

For all real numbers a, b, and c, the distributive property says that:


a(b + c) = ab + ac

We apply this property to get:


6 + 4.5(32f - 14f) = 6 + 4.5 * 32f + 4.5 * - 14f


6 + 4.5(32f - 14f) = 6 + 144f - 63f

We simplify the RHS to get:


6 + 4.5(32f - 14f) = 6 + 81f

User IronMan
by
4.9k points